The Influence of Gender Budgeting in Indian States on Gender Inequality and Fiscal Spending - Stotsky, Janet (IMF Working Papers; Working Paper ;, 2016)
This study investigates the effect of gender budgeting in India on gender inequality and fiscal spending. Gender budgeting is an approach to budgeting in which governments use fiscal policies and administration to address gender inequality and women's advancement. There is little quantitative study of its impact. Indian states offer a relatively unique framework for assessing the effect of gender budgeting. States with gender budgeting efforts have made more progress on gender equality in primary school enrollment than those without, though economic growth appears insufficient to generate equality on its own. The implications of gender budgeting for fiscal spending were more ambiguous.